Aggregated structures and their functionalities in hydrogels. Issue 2 (13th February 2021) - Cui, Kunpeng; Gong, Jian Ping
Abstract: Biological soft tissues and hydrogels belong to the same category of soft and wet matter. Both of them are composed of polymer network and a certain amount of water, and permeable to small molecules. Biological tissues possess elaborated structures and exhibit outstanding functionalities. On the other hand, hydrogels are usually amorphous with poor functionality. In recent years, various hydrogels with robust functionalities have been developed by introducing aggregated structures into the gel networks, widely extend their applications in diverse fields, such as soft actuators, biological sensors, and structural biomaterials. Four strategies are usually used to fabricate aggregated structure into hydrogels, including molecular self‐assembling, microphase separation, crystallization, and inorganic additives. Different aggregated structures entail the gel very different functionalities. A simple aggregated structure is able to bring multiple functionalities and a combination of mechanical performances of the hydrogels. In this review, we describe the strategies used to construct aggerated structure in hydrogels and discuss about the close relation between the aggregated structure and functionality. We also highlight the role of nonequilibrium aggregated structure in fabricating hydrogels with dynamic memorizing‐forgetting behavior and point out the remaining challenges. Abstract : Creating materials with elaborated structures and outstanding functionalities as biological tissues is a dream of material scientists. Hydrogel is one ideal candidate for such purpose as it has similar soft and wet nature as biological soft tissues. This review paper summarized the recent process in developing hydrogels with diverse aggregated structures and functionalities and pointed out the remaining challenges.